Monopoly on Marine and Fisheries Policy on Lobster Management in 2020 - Anggarini, Dhini; Dewi, Dian Suluh Kusuma (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2021)
Corruption case is related to re-permitting the export of lobster seeds as regulated in the Minister of Marine Affairs and Fisheries Regulation no. 12 of 2020 concerning the Management of Lobster, Crab, and Crab, underlie the research topic, namely the evaluation of fry export policies and evaluating the phenomenon of corruption. The results of this study are expected to be an input for the evaluation of public policies that should be able to solve problems, not even provide opportunities to harm the state and society. The purpose of this study is to examine the lobster management policies listed in Permen KP no. 12 of 2020. This research was conducted from November 2020-January 2021. The research method is descriptive qualitative by using literature studies in the form of literature reviews, theoretical studies, secondary data from pages of related agencies and mass communication media including online media such as the news portal and social media such as youtube. The analysis results are processed using the Nvivo 12 Plus application to help data accuracy. There have been several irregularities since the enactment of Permen KP No. 12 of 2020 concerning the Management of Lobster, Crab, and Crab starting May 4, 2020. Until 6 months after the enactment of the regulation, the Minister of Maritime Affairs and Fisheries Edhy Prabowo's Hand Catching Operation occurred in the case of bribery for lobster seed exports. as well as the abuse of power possessed by monopolizing policies to achieve what is desired, namely reaping benefits in the control of strategic potentials and investment opportunities for several actors.